Advanced concepts for intelligent vision systems : 15th International Conference, ACIVS 2013, Poznań, Poland, October 28-31, 2013. Proceedings / Jacques Blanc-Talon, Andrzej Kasinski, Wilfried Philips, Dan Popescu, Paul Scheunders (eds.) - Blanc-Talon, Jacques, 1962- (Lecture notes in computer science, 2013)
This book constitutes the thoroughly refereed proceedings of the 15th International Conference on Advanced Concepts for Intelligent Vision Systems, ACIVS 2013, held in Pozna?, Poland, in October 2013. The 63 revised full papers were carefully selected from 111 submissions. The topics covered are aquisition, pre-processing and coding, biometry, classification and recognition, depth, 3D and tracking, efficient implementation and frameworks, low level image analysis, segmentation, and video analysis.